Benefit sharing in genomic and biobanking research in Uganda: Perceptions of researchers and research ethics committee members - Mwaka, Erisa Sabakaki; Bagenda, Godfrey; Sebatta, Deborah Ekusai; Nabukenya, Sylvia; Munabi, Ian (Frontiers in Genetics, 2022)
Background: Global health research is increasingly placing emphasis on the need to translate genomic knowledge into products and policies. This has raised pertinent ethical, legal, and societal concerns for stakeholders such as sample or data ownership, commercialization, and benefit sharing. There is limited awareness of the concept of benefit sharing by stakeholders in sub-Saharan Africa. Objective: This study aimed to explore the perceptions of researchers and research ethics committee members on benefit sharing in international collaborative genomic and biobanking research. Methods: Qualitative in-depth interviews were conducted with 15 researchers and 19 research ethics committee members. A thematic approach was used to interpret the results. Results: Six themes emerged from the data and these included perceptions on the benefits of genomic and biobanking research; discussion of benefit sharing with participants during the informed consent process; legal implications of benefit sharing and the role of material transfer agreements; equity and fairness in sharing the benefits of genomic research; perceive barriers to fair benefit sharing; and recommendations for fostering fair and equitable benefit sharing in genomic and biobanking research. Respondents clearly understood the various forms of benefits of genomic and biobanking research and opined that such benefits should be fairly and equitably shared with low and middle-income country researchers and their institutions, and research communities. The perceived barriers to the fair benefit sharing unfavorable power disparities, weak research regulatory frameworks, and lack of scientific integrity. Conclusion: Overall, respondents felt that the ground was not leveled and there was neither equity nor fairness in the sharing of genomic and biobanking research benefits in collaborative research. For fair and equitable benefit sharing, we recommend capacity strengthening and empowering of research scientist in developing countries; strengthening regulatory systems and extending the mandate of research ethics committee in material transfer agreement development and implementation; and the meaningful involvement of local research communities in benefit sharing negotiations.